Biometric characteristics of eel Anguilla bicolor in Krueng Sawang River, North Aceh, Indonesia - Mulyadi, Mulyadi; Zulfikar, Zulfikar; Khalil, Munawar (Universitas Malikussaleh, 2025)
Eels are a valuable economic resource in both local and international markets due to their high nutritional content, particularly their rich vitamin and micronutrient profile. However, their populations face increasing threats from overfishing and habitat degradation, necessitating a deeper understanding of their distribution, growth patterns, and ecological characteristics. This study aimed to identify eel (Anguilla bicolor) species inhabiting the Krueng Sawang River, analyze their length-weight relationships, and assess biometric variations among different sampling locations. Fieldwork was conducted in April and May 2018 across three sampling stations in North Aceh District: Tanoh Anoe (Station 1), Gle Dagang (Station 2), and Babah Krueng (Station 3). A total of 100 eels were collected, with individuals from Station 1 averaging 50.17 cm in length and 237.78 g in weight, those from Station 2 averaging 31.96 cm in length and 135.93 g, and specimens from Station 3 averaging 35.18 cm in length and 148.21 g. Morphological analysis confirmed that all collected specimens belonged to A. bicolor, indicating a homogeneous population within the river system. The length-weight relationship analysis revealed a negative allometric growth pattern, suggesting that increases in length outpace weight gain. These findings provide valuable insights into the population dynamics of A. bicolor in North Aceh, offering essential baseline data for future conservation efforts and the development of sustainable fisheries management strategies.